ADOPTION OF CLIMATE-SMART AGRICULTURAL PRACTICES AMONG RICE FARMERS IN BOGORO AND DASS LOCAL GOVERNMENT AREAS OF BAUCHI STATE, NIGERIA - Sunday, G.; Babaji, A.U.; Bala, A.H. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study assessed the adoption of climate-smart agricultural practices (CSAPs) among rice farmers in Bogoro and Dass Local Government Areas of Bauchi State, Nigeria. A multi-stage sampling technique was used to select 240 respondents. Data were collected through questionnaires and analyzed using descriptive and inferential statistics. The findings revealed that 55% of respondents were male, 69.6% were married, and most (29.7%) were within the active working age of 36–45 years. About 31.3% and 20.8% of the respondents attained secondary and OND/NCE education, respectively. Additionally, 45% of the respondents had 6–10 years of farming experience while and 36.7% of the respondents had household sizes of 10–12 persons. Majority (67.1%) of the respondents were not members of cooperative societies. Friends and relatives, radio, and extension agents ranked 1st, 2nd, and 3rd, respectively, as sources of climate change information. Respondents demonstrated high awareness and adoption of CSAPs, particularly crop rotation (X̅ = 3.9), organic fertilizer use (X̅ = 3.9), and improved seed varieties (X̅ = 3.5). Major constraints were inadequate extension services (ranked 1st), high cost of seeds (2nd), drought, and rainfall shortage (3rd). The study concluded that the respondents adopted CSAPs at various levels of adoption. It is recommended that Government, through the Agricultural Development Programmes (ADPs) and extension agencies, should strengthen extension service delivery by recruiting, training, and deploying more agents to rural communities